Constitutional values in young Europeans: singularities by countries. - Amador Muñoz, Luis Vicente; Mateos Claros, Francisco; Esteban Ibáñez, Macarena; Olmedo Ruiz, Francisco Javier (IJERI: International Journal of Educational Research and Innovation, 2019)
This paper analyzes the European constitutional values of dignity, freedom, equality, solidarity, citizenship and justice, from the field of university youth in Germany, Great Britain, Spain, France, Italy and Portugal. It recognizes the values shared by all the European youth analyzed in general, and the singularities of each country and, in addition, the importance of education in citizen values, education for citizenship is appreciated. At first, a sampling was conducted in which subjects were sought from countries with different positions in their values and in their democratic traditions. The instrument used is a 58-item questionnaire in which values and sociopolitical attitudes are studied in young Europeans. Later, we applied the statistical technique of the factorial analysis of correspondences whose objective is to present in a perceptual map the information of the analyzed data from contingency tables. In the analysis we have seen how the opinions of young people differ in the categories of appreciation with which they have expressed their perception of each of the values studied, allowing a definitive approach to be made to the unique characteristics of each group or country. Through the constitutional values.